2016
DOI: 10.1002/jsfa.7606
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of bioactive collagen hydrolysates enhance facial skin moisture and elasticity and reduce facial ageing signs in a randomised double-blind placebo-controlled clinical study

Abstract: This study demonstrated that the use of the collagen hydrolysate with a higher content of Pro-Hyp and Hyp-Gly led to more improvement in facial skin conditions, including facial skin moisture, elasticity, wrinkles and roughness. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 23 publications
1
89
0
4
Order By: Relevance
“…Likewise, dietary supplementation with collagen hydrolysates (10 g/day) to 40-59 year-old women for 8 weeks increased collagen density in the dermis, while decreasing the fragmentation of the dermal collagen network, with the effects occurring at Week 4 and persisting through Week 12 (Asserin et al 2015). Furthermore, daily oral administration of 5 g of a collagen-hydrolysate food product (containing 0.1 or 2 g Pro-Hyp and Hyp-Gly per kg product) by 35-55 year-old women for 8 weeks resulted in dose-dependent improvements in facial skin conditions, such as skin moisture, elasticity, wrinkles, and roughness (Inoue et al 2016). Of particular interest, 12-month daily oral administration of 5 g collagen hydrolysates (containing 4-hydroxyproline) augmented bone mineral density in postmenopausal women (König et al 2018), suggesting their role in preventing osteoporosis.…”
Section: Health Benefits Of 4-hydroxyproline Supplementationmentioning
confidence: 99%
“…Likewise, dietary supplementation with collagen hydrolysates (10 g/day) to 40-59 year-old women for 8 weeks increased collagen density in the dermis, while decreasing the fragmentation of the dermal collagen network, with the effects occurring at Week 4 and persisting through Week 12 (Asserin et al 2015). Furthermore, daily oral administration of 5 g of a collagen-hydrolysate food product (containing 0.1 or 2 g Pro-Hyp and Hyp-Gly per kg product) by 35-55 year-old women for 8 weeks resulted in dose-dependent improvements in facial skin conditions, such as skin moisture, elasticity, wrinkles, and roughness (Inoue et al 2016). Of particular interest, 12-month daily oral administration of 5 g collagen hydrolysates (containing 4-hydroxyproline) augmented bone mineral density in postmenopausal women (König et al 2018), suggesting their role in preventing osteoporosis.…”
Section: Health Benefits Of 4-hydroxyproline Supplementationmentioning
confidence: 99%
“…Collagen hydrolysate is prepared from skin, bones, and tendons of animals, or the skin and scales of fish. In human trials with placebo controls, ingestion of collagen hydrolysate (2.5-10 g/day) suppresses transepidermal water loss, reduces wrinkle volume, and increases elasticity of skin [1][2][3][4]. Furthermore, ingestion of collagen hydrolysate moderates the symptoms of 2 of 9 osteoarthritis [5,6] and enhances healing of pressure ulcers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The biological responses of other collagen‐derived peptides (except Pro‐Hyp) are also important due to the potential occurrence of high biological activity even at low plasma concentrations, as well as the potential synergistic effects of various peptides. Consequently, skin cells responses can significantly differ when they are exposed to a single collagen‐derived peptide or a specific combination thereof (Liu et al, ; Inoue et al, ), contributing to explain these differences we found.…”
Section: Discussionmentioning
confidence: 67%
“…On the basis of clinical studies, daily oral supplementation of specific CH has been demonstrated to improve skin moisture and elasticity (Proksch et al, 2014b;Inoue et al, 2016) and reduce wrinkle volume in women skin (Proksch et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%